The importance of Method 300 to improve the mathematical foundation of first-year STEM Brazilian undergraduates - de Paulo, Gilcilene Sanchez [UNESP]; Dakuzaku, Mateus Mitsuo Goto [UNESP]; Ortega, Eliane Maria Vani [UNESP] (Modestum, 2024)
This research explores strategies to support first-year STEM Brazilian undergraduates in two programs, computer science and mathematics, through partnerships among faculty and student members and the implementation of an active methodology known as “Method 300” within an elementary mathematics course. The primary goal of these initiatives was to enhance the academic performance of freshmen. In Method 300, for students to benefit from grade improvements, they must assist each other, regularly attend team meetings, and commit to the activities that constitute the method. The method was implemented only during the first half of the course, fortunately it also implicated into the second part of the course, showing that a tenth of the students who performed poorly at the beginning achieved satisfactory and excellent performance in the last assessment, even though the content was more complex. According to the assessment system of the whole course, by monitoring students who initially had poor academic performance, it was found that half of them achieved satisfactory performance by the end of the course, which contributed to a final approval rate above 73% of all students. The condition of student heterogeneity is crucial for the effective application of Method 300; without it, this could become a potential limitation to its successful implementation. In addition to this strategy, the course was supported by voluntary extracurricular tutors, although these were underutilized by the freshmen, prompting us to consider new ways of providing support. These results suggest that future research in this field should focus on improving students’ academic performance by systematically replicating Method 300 in other courses for freshmen students.
Keywords: integration; meaningful learning; Method 300; STEM